Perbedaan Suara.com dan Hidayatullah.com dalam Memberitakan Rancangan Undang-Undang Penghapusan Kekerasan Seksual - Wahyudi, Eko; Rifa’i, Akhmad (Al-MUNZIR, 2023)
In 2020-2021 there has been much discussion of the pros and cons of the Draft Law on the Rancangan Undang-Undang Penghapusan Kekerasan Seksual (RUU-PKS) in online media. Each media has its own ideology, therefore this study aims to look at the framing of two media with different ideologies in reporting the RUU-PKS. The media are Suara.com and Hidayatullah.com where it can be seen that the media's attitude is in the form of pros or cons towards the RUU-PKS. This study uses a qualitative methodology of collecting news documents which are then taken as samples through a purposive sampling technique. Researchers used Zhondang Pan and Gerald M. Kosicki's framing analysis model to analyze the samples. Researchers found that Suara.com and Hidayatullah.com prioritize speed in providing information and prioritize media ideology so that it is very clear in giving partiality to the pros and cons. The findings are in the form of a comparative thing between the online media Suara.com and Hidayatullah.com. It was found that Suara.com sided with the ratification of the RUU-PKS. While Hidayatullah.com is on the opposite side of the ratification of the bill. This is shown by the way the two media forms framing, starting from giving titles, emphasizing facts, and so on. As online media whose content spreads quickly, Suara.com and Hidayatullah.com should consider whether their publications can make conditions worse or calm conditions.Keywords: Framing, Issues of RUU-PKS, Media Differences, Media Ideology